2012
DOI: 10.1007/s00223-012-9647-9
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects of Amino-Bisphosphonates on Circulating γδ T Cells

Abstract: The aim of this study was to explore whether desensitization to the occurrence of the acute-phase response (APR) in patients previously treated with amino-bisphosphonates (N-BPs) is due to a long-lasting reduction in the number of circulating γδ T cells. Circulating lymphocyte subpopulation counts were obtained from 63 patients with postmenopausal or senile osteoporosis at baseline and after 2 days and 12 months of the first intravenous (IV) 5 mg zoledronic acid (ZOL) infusion. At baseline both the proportion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 25 publications
4
45
0
Order By: Relevance
“…The repeated BP injections are postulated to result in the repeated activation of V␥9V␦2 T cells leading to eventual ␥␦ T cell depletion (17,18). It is tempting to speculate that the decreased circulating V␥9V␦2 T cells may causally associate with the development of nonexposure and fistula phenotype of ONJ in humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The repeated BP injections are postulated to result in the repeated activation of V␥9V␦2 T cells leading to eventual ␥␦ T cell depletion (17,18). It is tempting to speculate that the decreased circulating V␥9V␦2 T cells may causally associate with the development of nonexposure and fistula phenotype of ONJ in humans.…”
Section: Discussionmentioning
confidence: 99%
“…A deficiency in circulating ␥␦ T cells has been reported in patients with long term and repeated BP administrations (17,18), and BP-induced ␥␦ T cell deficiency was postulated to promote an underlying susceptibility to the development of ONJ (17). Because ␥␦ T cells are preferentially involved in barrier immunity (19,20), we hypothesized that the ␥␦ T cells in the oral barrier tissue play an important role in the development of ONJ.…”
Section: Osteonecrosis Of the Jaw (Onj)mentioning
confidence: 99%
“…Knowing that ZA is myelotoxic 12 and has effects on the number of circulating leukocytes (acutely and chronically) 20,21 we performed haematological analysis throughout the experimental protocol. Each week, beginning on the 6th day of the first dose of ZA, 2 mL of blood (retro-orbital plexus) was collected.…”
Section: Blood Collection and Analysismentioning
confidence: 99%
“…The latter is referred to as the acute phase response (APR) and it is linked to the activation of γδ T cells (in particular their major subpopulation of Vδ2 T cells) and the release of the pyrogenic cytokines such as IFN-γ and TNF-α 8. We observed that the proportion of circulating γδ T cells is an important determinant of the occurrence of APR after administration of N-BPs,9 and that N-BP treatment is associated with a decrease in circulating γδ T cells for at least 1 year,10 in particular in the patients with APR 11. The decrease in circulating γδ T cells could be attributed to the differentiation and homing at tissue levels of these cells 12.…”
mentioning
confidence: 67%